Expression and significance of Pim‐3 kinase in adult T‐cell leukemia. (11th September 2017) - Ishikawa, Chie; Senba, Masachika; Hashimoto, Tadashi; Imaizumi, Atsushi; Mori, Naoki
Abstract: Background: Human T‐cell leukemia virus type 1 (HTLV‐1) causes adult T‐cell leukemia (ATL). Viral Tax protein plays a major role in ATL development. Pim family of serine/threonine kinases is composed of Pim‐1, ‐2, and ‐3. The potential of Pim family as a target in ATL was analyzed. Methods: RT‐PCR and Western blotting were used to determine the expression of Pim kinases, Tax, and intracellular signal molecules. Knockdown of Pim‐3 and RelA was performed using small interfering RNA. The effects on cell proliferation, viability, cell cycle, and apoptosis were analyzed by WST‐8, propidium iodide, and APO2.7 assay. NF‐κB DNA binding activity was investigated by electrophoretic mobility shift assay. Results: Pim‐3 expression was restricted to HTLV‐1–infected T‐cell lines. Tax induced Pim‐3 expression through NF‐κB. Knockdown of Pim‐3 showed growth inhibition of HTLV‐1–infected T cells. NJC97‐NH, a novel inhibitor of the Pim‐1/3 kinases, inhibited cell viability. NJC97‐NH induced G2/M cell cycle arrest associated with downregulation of cyclin A and cyclin B1 expression, as well as apoptosis accompanied with downregulation of XIAP and Mcl‐1 expression through inhibition of NF‐κB pathway, mediated through decrease in IκBα and RelA phosphorylation. Conclusion: Pim‐3 is a potentially suitable target for the development of novel therapeutic agents against ATL.